2000
DOI: 10.1152/ajpregu.2000.279.6.r2208
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory interactions during resistive load breathing

Abstract: The addition to the respiratory system of a resistive load results in breathing pattern changes and in negative intrathoracic pressure increases. The aim of this study was to use resistive load breathing as a stimulus to the cardiorespiratory interaction and to examine the extent of the changes in heart rate variability (HRV) and respiratory sinus arrhythmia (RSA) in relation to the breathing pattern changes. HRV and RSA were studied in seven healthy subjects where four resistive loads were applied in a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 16 publications
3
26
1
Order By: Relevance
“…Hyperventilation impairs baroreflex modulation of HR and sympathetic nerve traffic (115). A change in respiratory pattern, for example during resistive load breathing, may itself affect respiratory sinus arrhythmia, independent of the arterial pressure changes accompanying respiration (11).…”
Section: Physiology Of the Baroreflex And Methods To Explore Its Funcmentioning
confidence: 99%
“…Hyperventilation impairs baroreflex modulation of HR and sympathetic nerve traffic (115). A change in respiratory pattern, for example during resistive load breathing, may itself affect respiratory sinus arrhythmia, independent of the arterial pressure changes accompanying respiration (11).…”
Section: Physiology Of the Baroreflex And Methods To Explore Its Funcmentioning
confidence: 99%
“…Calabrese et al (7) have shown that adding resistive loads throughout the entire breathing cycle, hence increasing negative ITP swings, resulted in an increase in total power of HRV. Noteworthy, the increase in HRV appeared to be correlated to an increase in the respiratory period during resistive breathing rather than due to changes in ITP.…”
Section: Interpretation Of Changes In Hrvmentioning
confidence: 99%
“…Resistive loads were added throughout the entire breath and for each recording, the value of the resistance was calculated from the mouth pressure versus flow plot throughout the total recording. The mean value (±SD) for all resistances on the 11 subjects were at rest R 0 = 0.75 (±0.03) for the apparatus resistance, R 1 = 3.26 (±0.25), R 2 = 5.27 (±0.34), R 3 = 8.23 (±0.43) and R 4 = 12.26 (±0.63) cm H 2 O l -1 s. The recordings were performed in a random order unknown to the subject and on two subjects (#4 and #10) only four recordings were performed (Calabrese et al 2000).…”
Section: Validation With Experimental Datamentioning
confidence: 99%